Pentingnya Pendidikan Demokrasi di Indonesia dalam Menghadapi Era Digital - Zahro Rohmatin; Alif M Taufiq; Naeli Anggi Nurmadina; Rafi Rizqullah; Hamdi Abdullah Hasibuan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Democracy education in the digital era is an important effort to strengthen democratic values and increase active participation in political life. In the digital era, information and communication technology has facilitated the quick and easy dissemination of information, thereby increasing citizens' ability to influence government policy. However, challenges such as disinformation and online polarization also arise, so collective efforts need to be made to strengthen digital democracy. Using digital technology wisely is also important. Increasing digital literacy so that people can identify fake news, understand social media algorithms, and protect online privacy is a significant first step. Strong regulation is also needed to ensure that algorithms and business practices do not support the spread of disinformation or exacerbate polarization. With good democratic education and smart use of digital technology, hopes are high that digital democracy can deepen democratic engagement, not reduce it. This article will discuss how democratic education can increase community participation and strengthen democratic values in the digital era.